Incidence and risk factors for surgical site infection following enucleation in dogs - Dacanay, Samantha J.; Barber, Renee M.; Diehl, Kathryn A.; Myrna, Kathern E. (Frontiers in Veterinary Science, 2023)
Surgical site infections (SSI) increase morbidity, increase treatment costs, and can delay onset of necessary adjunctive therapy. The goal of this retrospective study was to determine the incidence of and risk factors of SSI after enucleation in dogs. Medical records were searched at one veterinary teaching hospital and identified 280 dogs that underwent enucleation and had an adequate follow-up to assess SSI. Multiple pre-operative (e.g., reason for enucleation), peri-operative (e.g., surgical approach and surgeon experience level), and post-operative (e.g., use of post-operative antibiotics or anti-inflammatory medications) variables were assessed as risk factors for development of SSI. The incidence of SSI after enucleation was 5%, and no risk factors for SSI were identified. Dogs that received cephalexin as a prophylactic post-operative antibiotic were statistically more likely to develop SSI versus those that received a different post-operative antibiotic (p = 0.045). However, the clinical significance of this finding is unclear as administration of prophylactic post-operative antibiotics overall did not reduce the risk of SSI in the population evaluated here.